Percutaneous transluminal angioplasty procedure for central venous stenosis inpatient undergoing hemodialysis in Pelni Hospital: case series - Muhammad Zaini Azwan; Anak Agung Ngurah Nata Tresnawan Putra (Indonesian Vascular Access Association (IVAA), 2021)
Introduction: Many causes leads to kidney impairment. This does not rule out the increasing number of patients undergoing hemodialysis. The common vascular access used during hemodialysis is an arteriovenous fistula (AVF). The arteriovenous fistula was preferred because it lasts longer and has a lower risk of infection for vascular access, meanwhile central venous stenosis or occlusion in the vein that carries the blood from the extremities to the heart often occur. If vascular access is still used during hemodialysis in which central venous stenosis is formed, it needs to make a new vascular access option. Percutaneous transluminal angiography (PTA) main objectives are to dilate the venous lesion that has occlusion more than 50% and extending the lifespan of arteriovenous fistula. In this case, we report six patients hemodialysis with central venous stenosis treated with percutaneous transluminal angiography. This procedure has benefits that are arteriovenous fistula can be used again to reach hemodialysis adequacy optimally and reduce pain and swelling in the arms. Case description: There six cases who were 45,48,57.58,63 and 66 years old who underwent percutaneous transluminal angioplasty procedures for central venous stenosis. Several past illnesses of the patients underlying the kidney impairment such chronic hypertension, chronic coronary heart complications, and/or diabetes. Several patients felt AVF swollen and/or painful. Minimal residual stenosis after balloon angioplasty was performed. Conclusion: According to our cases, patients that underwent the hemodialysis felt swollen or/and pain due to stenosis ballooning angioplasty help minimize the residual stenosis.